Estimation of Earnings- and Schooling Choice Relations: A Likelihood Approach - John K. Dagsvik; Torbjørn Hægeland; Arvid Raknerud (Statistics Norway, Research Department, 2006)
In this paper we develop a full information maximum likelihood method for the estimation of a joint model for the choice of length of schooling and the corresponding earnings equation. The model for schooling is assumed to be an ordered probit model, whereas the earnings equation is allowed to be very general with explanatory variables that are flexible transformations of schooling and experience. The coefficients associated with length of schooling and experience are allowed to be random and all the random terms of the model may be correlated. Under normality assumptions, we show that the joint probability distribution for schooling and earnings can be expressed on a closed form that is tractable for empirical analysis.
Keywords: C31; I20; J30; 330; Schooling choice; earnings equation; treatment effects; self-selection; ordered probit; random coefficients; full information maximum likelihood